Development And Challenges of Telematics Law in The Digital Era in Indonesia - Puannandini, Dewi Asri; Nadapdap, Binton Jhonson (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study aims to examine telematics law in Indonesia, from regulatory, implementation, and challenges in the digital era. Telematics law, which covers laws regulating the use of information and communication technology (ICT), has become increasingly important as digital technology evolves. Using a qualitative approach, this paper explores how telematics law is applied in Indonesia and the challenges and solutions in its implementation. The study also analyzes relevant laws and practices in regulating the use of information technology in Indonesia. The findings show that although the regulations exist, the implementation and public understanding of telematics law need to be improved.